Hypomorphic function and somatic reversion of DOCK8 cause combined immunodeficiency without hyper IgE - Kienzler, A; van Schouwenburg, P; Taylor, J; Marwah, I; Sharma, R; Noakes, C; Thomson, K; Sadler, R; Segal, S; Ferry, B; Taylor, J; Blair, E; et al. (Elsevier, 2015)
Highlights: Whole exome sequencing identified the underlying defect in a patient with combined immunodeficiency. A novel compound heterozygous DOCK8 mutation was identified. Expression of a truncated DOCK8 protein with hypomorphic function was identified. Somatic reversion of DOCK8 mainly in T cells was identified. DOCK8 deficiency may present without severe viral infections and increased serum IgE levels. Abstract: Loss of function mutations in DOCK8 are linked to hyper-IgE syndrome. Patients typically present with recurrent inopulmonary infections, severe cutaneous viral infections, food allergies and elevated serum IgE. Although patients may present with a spectrum of disease-related symptoms, molecular mechanisms explaining phenotypic variability in patients are poorly defined. Here we characterized a novel compound heterozygous mutation in DOCK8 in a patient diagnosed with primary combined immunodeficiency which was not typical of classical DOCK8 deficiency. In contrast to previously identified mutations in DOCK8 which result in complete loss of function, the newly identified single nucleotide insertion results in expression of a truncated DOCK8 protein. Functional evaluation of the truncated DOCK8 protein revealed its hypomorphic function. In addition we found somatic reversion of DOCK8 predominantly in T cells. The combination of somatic reversion and hypomorphic DOCK8 function explains the milder and atypical phenotype of the patient and further broadens the spectrum of DOCK8-associated disease.